Prevalence of ultra-processed foods and beverages in newly launched products across the Americas: a comparison between the United States and Latin American countries from 2018 to 2023 - Vatavuk-Serrati, Gabriela; Meyer, Katie A.; Miles, Donna R.; Taillie, Lindsey Smith (Frontiers in Public Health, 2025)
BackgroundUltra-processed foods (UPFs) are an increasing global health concern, but their prevalence across the food supply is unknown. This is particularly important in developing countries such as Latin America, where consumption is lower but increasing. We quantified country-specific metrics of UPFs in the food supply across the Americas, including the prevalence of UPFs, the presence and number of additives, and the extent to which UPFs and non-UPFs are high in saturated fat, sugar, and sodium (HFSS).MethodsUsing data on packaged products launched between 2018 and 2023 from the Mintel Global New Products Database in 11 North and Latin American countries (n = 207,363 products), we identified the presence of ultra-processing markers, such as additives, in foods and beverages’ ingredient lists. We compared the prevalence of UPFs and food additives in each country to the U.S. and the mean number of additives by additive class and country. The prevalence of HFSS for ultra-processed and non-ultra-processed packaged foods and beverages was estimated in a subsample (n = 123,072) based on the Chilean nutrient profile model.ResultsThe prevalence of UPFs ranged from 69 in Venezuela to 85% in Costa Rica. Flavors and other additives were the most prevalent, ranging from 60 to 78% and 49 to 70% in Venezuela and Costa Rica, respectively. The mean number of additives ranged from 3.9 in Venezuela to 7.1 in Peru. For foods, but not beverages, a higher percentage of ultra-processed products were HFSS compared to non-ultra-processed products.ConclusionThe prevalence of UPFs among newly launched products is high across all countries in the Americas. Policies are needed to create healthier food supplies in the region.